Visual metaphor of Guyub Rukun batik motifs: Symbolizing the personal style, spirituality, and fashion identity of Margomulyo Bojonegoro Village Head - Sugeng Wardoyo; Tri Wulandari; I Made Sukanadi (Universitas Dian Nuswantoro, 2025)
The purpose of this research was to create a jarik cloth with a visual metaphor of Guyub Rukun batik motifs used by the regional head of Margomulyo village as a fashion identity. The visual metaphor of the Guyub Rukun batik motif reflects Samin's cultural values and noble teachings. This research contributes to the realization of Guyub Rukun jarik cloth as a medium for preserving and strengthening the noble teachings of Samin Margomulyo Bojonegoro in the context of sustainable tradition, culture, and the times. The creation of the jarik was inspired by the value of Surosentiko's Samin noble teachings. The village head is a leadership figure symbolizing harmony and protection of the Margomulyo village community. The Margomulyo village leader has a personal style and spiritual belief in applying the noble teachings of Samin in his leadership to achieve peace, tranquility, togetherness, and prosperity in the community’s social life. The village leader is responsible for preserving the Samin Margomulyo cultural tradition. This research design uses practice-based research, visual metaphor, and vehicle transfer (adaptation). The stages of this research began with observation, data collection, data analysis, and presentation of the analysis results. The results of the analysis were used to conceptualize the design of batik motifs and continued the process of embodiment of the jarik cloth. The result of the design is a prototype of Guyub Rukun jarik as a socio-cultural identity and its main function as the clothing of the Margomulyo village leaders.